Immunoprotective effects of a hemin‐binding peptide derived from hemagglutinin‐2 against infection with Porphyromonas gingivalis. (9th November 2017) - Zhu, Y.C.; An, T.; Liu, Y.; Zhang, Z.L.; Yang, Q.B.
Summary: The principal etiologic agent in periodontal disease, Porphyromonas gingivalis, generates cysteine proteases that bind heme with domains such as hemagglutinin‐2 (HA2). High‐affinity HA2–hemin binding supplies the porphyrin and ferric iron needed for growth and virulence. The DHYAVMISK peptide, recently identified at the hemin‐binding site of HA2, inhibits hemin binding. We now evaluate the protective effect of vaccination with DGFPGDHYAVMISK (termed DK) against P. gingivalis using a rat infection model. Rats immunized with DK generated anti‐peptide serum IgGs and salivary sIgAs (as measured by ELISA). In a subcutaneous abscess model, the protective effect of immunization was then investigated by measuring abscess size following subcutaneous injection with P. gingivalis . In an oral infection model, a ligature inoculated with P. gingivalis was used to induce periodontitis. The degree of bone erosion, ordinarily provoked by infection, was then evaluated by micro‐computed tomography. We found that anti‐peptide antibody titers of serum IgGs and salivary sIgAs for rats immunized with DK and adjuvant were significantly higher than for sham‐immunized rats (injected with adjuvant/PBS alone; P < .05). In the subcutaneous abscess model, the DK + adjuvant‐vaccinated rats recovered faster than sham‐vaccinated animals, with their abscess sizes significantly smaller ( P < .05). Further, in the experimental periodontitis model, bone loss at the molar palatal side for DK + adjuvant‐vaccinated rats was significantly lower than for sham‐vaccinated animals ( P < .05). Collectively, these data demonstrate the potential of (DK) peptide immunization in terms of eliciting an immunoprotective effect against infection with P. gingivalis .